Surface disinfection efficacy and effectiveness assessment for low-resource outbreak settings. - Gallandat, Karin. (Tufts University. Tisch Library., 2019)
Infectious diseases are caused by pathogens such as bacteria, viruses, or parasites, and can be transmitted by contaminated surfaces. In outbreaks, this transmission pathway can be interrupted by various interventions including disinfection. Infectious diseases such as the Ebola virus disease (EVD) and cholera, disproportionately affect low-income countries. Current guidelines for disinfection in response to EVD and cholera outbreaks are inconsistent in terms of recommended pre-cleaning procedures and chlorine concentration. One reason for these inconsistencies is the lack of evidence to inform disinfection in low-resource outbreak settings. The goal of this dissertation was to contribute to the evidence base regarding the laboratory efficacy and field effectiveness of disinfection in Ebola and cholera contexts. Five projects were conducted, including : 1) a systematic review of the literature on surface disinfection efficacy, focusing on the identification of data applicable to low-resource settings; 2) the identification of an appropriate surrogate for the Ebola virus; 3) a laboratory-based efficacy evaluation of recommendations for surface disinfection in Ebola outbreaks using the surrogate; 4) a laboratory-based efficacy evaluation of surface disinfection in cholera outbreaks using Vibrio cholerae; and, 5) two field-based evaluations of household spraying - a disinfection intervention commonly implemented in response to cholera outbreaks. Results from this research provide insights into surface disinfection efficacy and effectiveness in conditions relevant to low-resource outbreak settings and were used to formulate concrete recommendations for the optimization and harmonization of surface disinfection interventions in response to EVD and cholera outbreaks. This work also led to the following considerations: • A trade-off exists between the standardization of laboratory methods and the evaluation of conditions relevant to outbreak settings; • Surrogate organisms can be instrumental to investigate surface disinfection efficacy; • Laboratory and field evaluations are complementary, but laboratory and field evidence may need to be reconciled; • The identification of relevant research questions requires the involvement of multiple stakeholders, including researchers, responders, and policy makers; • Evaluating existing recommendations is valuable, however researchers could have a proactive role in improving preparedness and developing novel response approaches. While the global burden of infectious diseases has been decreasing, populations in developing countries are still disproportionately affected and infectious disease outbreaks are expected to become increasingly frequent due to greater connectivity, population movements, and climate change. Further research is needed to improve preparedness and protect vulnerable populations.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Civil Engineering.; Advisor: Daniele Lantagne.; Committee: David Gute, Richard Johnston, and Tim Julian.; Keyword: Environmental health.